Skin rejuvenation by microneedle fractional radiofrequency and a human stem cell conditioned medium in Asian skin: a randomized controlled investigator blinded split-face study - Seo, Kyu Young; Kim, Dong Hyun; Lee, Sang Eun; Yoon, Moon Soo; Lee, Hee Jung (Journal of cosmetic and laser therapy, 2013)
Abstract Background and objectives: For skin rejuvenation, microneedle fractional radiofrequency (RF) is a recently developed minimally invasive method for delivering RF energy directly into the skin using microneedle. Additionally, the use of growth factors in skin rejuvenation is emerging as a novel anti-aging treatment. We evaluated efficacy and safety of microneedle fractional RF for skin rejuvenation, and furthermore the synergistic effect of stem cell conditioned medium, composed of a large number of growth factors and cytokines. Materials and methods: Fifteen females were included for a split-face comparative study with a blinded response evaluation. One side of each subject's face was treated with fractional RF alone, and the other side was treated with fractional RF plus stem cell conditioned medium. Patients received 3 sessions of treatment at 4-week intervals. Results: All patients showed clinical improvement on physician's global assessment and patient satisfaction scores on both sides of their faces. Among objective biophysical measurements, improvement in hydration, melanin, erythema index and especially skin roughness was noticed. Stem cell conditioned medium provided a synergistic effect on improvement of skin roughness, which was statistically significant (p <0.05). Histologic examination revealed marked increase in dermal thickness and dermal collagen content. Side effects were minimal. Conclusion: Microneedle fractional RF is a safe and effective skin rejuvenation method, and the better results may be expected when combined with stem cell conditioned medium.